Differences in obesity between the groups consuming snacks and breakfast habits in Universitas Islam Negeri Sumatera Utara Medan - Tri Niswati Utami; Lita Sri Andayani; Eliska Eliska; Susilawati Susilawati; Zuhrina Aidha; Reni Agustina Harahap (Journal of Community Empowerment for Health, 2022)
Overweight and obesity are increasing in Indonesia, and these conditions pose a growing threat to people with non-communicable diseases. This study aimed to show the difference in obesity among respondents who consume snacks compared to respondents who have the habit of eating breakfast with three choices to select from: always, sometimes, or never. This comparison was done to analyze the relationship between breakfast habits and snack consumption. This cross-sectional study collected data using a survey on 26 – 27 November 2021. The sample population included the entire academic community of the Universitas Islam Negeri Sumatera Utara, Medan. The sample was determined by an accidental sampling technique. Research instruments were used in the form of questionnaires, microtoise and weight scales to measure the anthropometrics of height and weight. Descriptive data analysis used normality tests and because the data were not normally distributed, the Kendall and Kruskal Wallis tests were done. The results of this study indicated that 38 respondents have overweight status (17.9%), 36 respondents (17.0%) obesity I, 18 respondents (8.5%) obesity II, and 26 respondents (12.3%) underweight. There was no significant difference in obesity among respondents who have the habit of eating breakfast always, sometimes, and never, with p-value of 0.793.There was a significant difference in obesity among respondents who have the habit of eating snacks never, sometimes, and always with a p-value of 0.014. Although snacking can sometimes lead to obesity, generally the fatting types of snacks consumed are cakes and fried foods. In conclusion, limiting snack foods such as cakes and fried foods can reduce obesity. It is recommended to replace the consumption of these snacks with fruits and vegetables.